A Proposed Decision Support System to Sustainable Production of Rice Using GIS Tools - Das, Swarup (International Journal of Computer Sciences and Engineering, 2025)
Rice is an important crop in the world and India holds the second position among the rice producing country. As the population increases day by day and the total cultivating land is remains fixed, the demand is getting high whereas production remains almost constant. So in this paper a GIS based decision support system for rice production is proposed to increase the yield of production. The system takes data related to ongoing practice of rice cultivation and different parameters which affects the production of rice, store these data to a database and helps to take decision in an efficient manner.